Corrections to “Fuzzy Logic-Based Substitution-Box for Robust Medical Image Encryption in Telemedicine” - Abdul Razaq; Louai A. Maghrabi; Musheer Ahmad; Farrah Aslam; Wei Feng (IEEE Access)
Presents corrections to the paper, Corrections to “Fuzzy Logic-Based Substitution-Box for Robust Medical Image Encryption in Telemedicine”.